2005
DOI: 10.1002/jnr.20606
|View full text |Cite
|
Sign up to set email alerts
|

Critical interval of somal calcium transient after neurite transection determines B104 cell survival

Abstract: Nerve cells may survive or die after axonal or dendritic transection. After neurite transection near (<50μm) the cell body of Fura-2 loaded B104 neuroblastoma (rat brain derived) cells, the somal calcium concentration (SCC) undergoes a three-phase transient change: a rapid (0 to 0.15 min posttransection (PT)) rise phase followed by an early (0.15 to 1.5 min PT) rapid decay phase, succeeded by a late (1.5 to 60 min PT) slower decay phase that restores SCC to preinjury levels. The SCC in a critical interval (1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 55 publications
(69 reference statements)
4
35
0
Order By: Relevance
“…We then added 3 kDa Texas Red dextran at 0 min PC (i.e., after neurite transection) to assess sealing. As reported previously (Yoo et al, 2003(Yoo et al, , 2004Nguyen et al, 2005), cells with transected neurites identified by their relationship to the score mark were always filled with fluorescein dextran (Fig. 1 B, E), whether or not they excluded Texas Red dextran.…”
Section: B104 Cells B104 Cells Derived From a Cns Neuroblastomasupporting
confidence: 82%
See 4 more Smart Citations
“…We then added 3 kDa Texas Red dextran at 0 min PC (i.e., after neurite transection) to assess sealing. As reported previously (Yoo et al, 2003(Yoo et al, , 2004Nguyen et al, 2005), cells with transected neurites identified by their relationship to the score mark were always filled with fluorescein dextran (Fig. 1 B, E), whether or not they excluded Texas Red dextran.…”
Section: B104 Cells B104 Cells Derived From a Cns Neuroblastomasupporting
confidence: 82%
“…As further confirmation of the validity of our single-dye assessment technique, when transection distance was not taken into account, the percentage of cells that sealed in the present study at 5, 20, and 60 min PC was not significantly ( p Ͼ 0.05, CMH 2 ) different than that in previous studies in which fluorescein dextran was used as an additional indicator of cells that were transected, but transection distance was not noted (Yoo et al, 2003;Nguyen et al, 2005). Hence, in all protocols described below, we used a single dye (Texas Red dextran) to assess dye exclusion as a measure of plasmalemmal sealing of transected B104 neurites.…”
Section: B104 Cells B104 Cells Derived From a Cns Neuroblastomasupporting
confidence: 82%
See 3 more Smart Citations